Alat Pengukur Tinggi Badan Digital Untuk Daerah Blankspot Internet - Auliyaa Azhari; Riki Mukhaiyar (Jurnal Teknik Elektro Indonesia, 2023)
Puskesmas is the first level of service which is the spearhead in efforts to improve public health. especially in remote areas, puskesmas where all health activities take place. Height measurement is one of the programs carried out at the puskesmas. However, with inadequate facilities, the height measurement process does not get maximum results. At this time, technological developments have produced many tools to help humans lighten their workload. One of the solutions given to overcome this manual measurement problem is to create a digital measurement tool based on internet access. The internet system is used so that users do not need to record measurement results manually. However, is this a solution for internet blankspot areas? In fact, Indonesia still has around 45% of areas that have not been reached by internet access or blankspots. Therefore by taking advantage of technological developments, the authors designed a digital height measuring device that is connected to a thermal print. It is intended that users can perform measurements automatically and obtain accurate results. Also, this tool aims to allow users to obtain measurement results immediately after the measurement activities have been completed by printing the results on a thermal printer without requiring an internet connection. The design of a tool that is small and uses a battery is intended so that measurements can be carried out by anyone and anywhere.